The Perception of Gender Equality Practices among CV Milzam Multi Sejahtera Jember Employees - Widayanti, Nike; Hidayat, Nurul; Handayani, Baiq Lily (Jurnal ENTITAS SOSIOLOGI, 2018)
The purpose of this study is to describe the practice of gender equality for plywood mill employees at CV Milzam Multi Sejahtera in Jember. The method used is a qualitative method with a feminist social science approach. The researcher selects the informants by using purposive techniques, with the criteria of workers who have worked in factories at least one year. Data collection techniques are done by observation, in-depth interviews, and documentation. Test the validity of the data using triangulation techniques. The analysis technique uses the interactive model of Miles and Huberman. The theory used is the Marxist / Socialist feminist theory. The results of the study show that: 1) In a work distribution system because women are considered to have a cautious nature, they are given easy jobs, but require accuracy, while work for men requires heavy work. 2) In the salary system, women are considered cheap labor, so they deserve a cheap salary. It is because the involvement of women in this work is only a side job. 3) Right to leave, the company does not distinguish between leave rights for male and female workers. However, workers who were given leave did not receive a replacement salary. 4) Promotion of position. Anyone can obtain the development of jobs by the requirements for appointment. So, based on research results at the CV Milzam Multi Sejahtera Jember plywood factory, there is relatively no gender inequality. Keywords: Perception, Equality Practices, Gender, Workers, Factory Referensi: Afrizal, M.A, 2014. Metode Penelitian Kualitatif: Sebuah Upaya Mendukung Penggunaan Penelitian Kualitatif dalam Berbagai Disiplin Ilmu. Jakarta: PT Raja Grafindo Persada. Fakih, Mansour.1996. Analisis Gender dan Transformasi Sosial. Yogyakarta: Pustaka Belajar. Cet 1. Husni, Lalu. 2006. Pengantar Hukum Ketenagakerjaan Indonesia. Jakarta: PT RajaGrafindo Persada. Makarao, Nurul Ramadhani. 2009. Gender dalam Bidang Kesehatan. Bandung: Alfabeta. Cet 1. Rokhmansyah, Alfian. 2016. Pengantar Gender dan Feminisme: Pemahaman Awal Kritik Sastra Feminisme. Yogyakarta: Garudhawaca. Sastrohadiwiryo, Siswanto. 2005. Manajemen Tenaga Kerja Indonesia. Jakarta: PT Bumi Aksara. Cet 3. Soepomo, Iman. 1992. Pengantar Hukum Perburuhan. Jakarta: PT. Ikrar Mandiriabadi. Tong, Putnam Rosemarie. 1998. Feminis Thought: Pengantar Paling Komprehensif kepada Arus Utama Pemikiran Feminis. Terjemahan Aquarini Priyatna Prabasmoro. Yogyakarta:Jalasutra.